DESIGN AND IMPLEMENTATION OF A DIGITAL MARKETING INFORMATION SYSTEM FOR KOHAN_YA (HANS JAYA GARMENT SME) - Ilham Rizky Almahdi; Hindarto Hindarto; Sumarno Sumarno; Hamzah Setiawan (Journal of Artificial Intelligence and Digital Economy, 2026)
Objective: This study aims to design and implement a web-based information system for KSI Hansjaya, a garment production business, to serve as both an information dissemination medium and an efficient online promotional tool. Method: The system development process followed the Software Development Life Cycle (SDLC) using the Waterfall model, which includes stages such as requirements analysis, system design, implementation, testing, and maintenance. The system accommodates two user categories: administrators and general users. Results: The system features were tested and evaluated through functionality testing and a questionnaire distributed to 20 respondents. The results showed that 70% of respondents strongly agreed, and 30% agreed that the system is feasible as a digital promotion medium, with all features functioning optimally according to user requirements. Novelty: This web-based system offers a responsive single-page website interface that allows administrators to manage product categories, details, and company contact information, while general users can access product information, ordering guidelines, and contact details. The developed website significantly supports KSI Hansjaya’s promotional activities and contributes positively to the business’s digital growth.